IMPROVING STUDENTS' REPRESENTATIONAL SKILL AND GENERIC SCIENCE SKILL USING REPRESENTATIONAL APPROACH - Sutopo - (Universitas Negeri Malang, 2013)
Abstract: Improving Students' Representational Skill and Generic Science Skill Using Representational Approach. This one group pretest-posttest research aimed to examine the effectiveness of representational approach to improve students' representational and generic science skills through Selected Topics of School Physics course. The subjects consisted of 24 undergraduate students of physics education program of UM. The data were gathered using integrated Mechanics Baseline Test and rubric. Quantitative data analyses included t-test, Cohen's d-effect size, and normalized gain, whereas qualitative data analyses included coding, tabulating, and interpreting. This result indicated that this representational approach was considered effective to achieve both learning outcomes. Abstrak: Meningkatkan Kemampuan Representasi dan Kecakapan Generik Sains Mahasiswa melalui Pendekatan Representasional. Penelitian one group pretest-posttest ini bertujuan menguji keefektifan pendekatan representasional untuk meningkatkan kemampuan representasi dan kecakapan generik sains mahasiswa calon guru fisika melalui matakuliah Kapita Selekta Fisika Sekolah. Subjek terdiri atas 24 mahasiswa S-1 program studi Pendidikan Fisika UM. Data digali melalui tes dasar mekanika dan  rubrik. Analisis kuantitatif meliputi t-test, effect size, dan gain ternormalisasi, sedangkan analisis kualitatif meliputi pengodean, penabelan, dan penafsiran. Penelitian menyimpulkan bahwa pendekatan representasional tersebut efektif mencapai tujuan yang diharapkan.